Knowledge of and adherence to radiographic guidelines for low back pain: a survey of chiropractors in Newfoundland and Labrador, Canada. - De Carvalho, Diana; Bussières, André; French, Simon D.; Wade, Darrell; Brake-Patten, Debbie; O'Keefe, Lino; Elliott, Barbara; Budgell, Ken; O'Reilly, Sara; To, Daphne; Hall, Amanda (Chiropractic & Manual Therapies, 2021)
Background: Low back pain (LBP) rarely requires routine imaging of the lumbar spine in the primary care setting, as serious spinal pathology is rare. Despite evidence-based clinical practice guidelines recommending delaying imaging in the absence of red flags, chiropractors commonly order imaging outside of these guidelines. The purpose of this study was to survey chiropractors to determine the level of knowledge, adherence to, and beliefs about, clinical practice guidelines related to the use of lumbar radiography for LBP in Newfoundland and Labrador (NL), Canada. Methods: A cross-sectional survey of chiropractors in NL (n = 69) was conducted between May and June 2018, including questions on demographics, awareness of radiographic guidelines, and beliefs about radiographs for LBP. We assessed behavioural simulation using clinical vignettes to determine levels of adherence to LBP guideline recommendations. Results: The response rate was 77% (n = 53). Half of the participants stated they were aware of current radiographic guideline recommendations, and one quarter of participants indicated they did not use guidelines to inform clinical decisions. The majority of participants agreed that x-rays of the lumbar spine are useful for patients with suspected pathology, are indicated when a patient is non-responsive to 4 weeks of conservative treatment for LBP, and when there are neurological signs associated with LBP. However, a small proportion indicated that there is a role for full spine x-rays (~ 21%), x-rays to evaluate patients with acute LBP (~ 13%), and that patient expectations play a role in decision making (4%). Adherence rate to radiographic guidelines measured using clinical vignettes was 75%. Conclusions: While many chiropractors in this sample reported being unsure of specific radiographic guidelines, the majority of respondents adhered to guideline recommendations measured using clinical vignettes. Nonetheless, a small proportion still hold beliefs about radiographs for LBP that are discordant with current radiographic guidelines. Future research should aim to determine barriers to guideline uptake in this population in order to design and evaluate tailored knowledge translation strategies to reduce unnecessary LBP imaging.